Concerning F. Gladkov’s Stand irr the Literary Struggle of the Twenties - Čepelytė, D. (Literatūra, 1969)
The essay „Concerning F. Gladkov’s stand in the literary struggle of the twenties" deals with F. Gladkov’s bonds with „Kuznitsa" (the oldest circle of proletarian writers) and with his arguments with RAPP on important literary questions. The author proves that F. Gladkov saw eye to eye with „Kuznitsa" and that’s why it is wrong to contrast them.